Enhanced Production of High‐Value Cyclopropane Fatty Acid in Yeast Engineered for Increased Lipid Synthesis and Accumulation. Issue 4 (18th October 2018) - Peng, Huadong; He, Lizhong; Haritos, Victoria S.
Abstract : The unique strained ring structure in cyclopropane fatty acids (CFA) conveys oxidative stability and lubricity to lipids. These attributes are highly valuable for industrial applications such as cosmetics and specialist lubrication but there is currently no commercial source of the lipid. Here, built on recently engineered strains of Saccharomyces cerevisiae, the authors have developed an efficient strategy for CFA production. Expression of the Escherichia coli cyclopropane fatty acid synthetase ( Ec.CFAS ) in the engineered yeast resulted in formation of cis ‐9, 10‐methylene‐hexadecanoic and octadecanoic acids in both the phospholipid (PL) and triacylglycerol (TAG) fractions. CFA concentration in TAG of engineered yeast is 12 mg CFA g −1 DCW (fourfold above the strain expressing CFAS only). The yield of CFA increases from 13.2 to 68.3 mg L −1, the highest reported in yeast, using a two‐stage bioprocess strategy that separated cell growth from the lipid modification stage. Strategies for further improvement of this valuable lipid are proposed. Abstract : Cyclopropane fatty acids (CFA) show great potential in high‐value cosmetics and specialist lubrication applications. The authors demonstrated that lipid pathway engineering designed for standard fatty acids also greatly improved CFA content and yield in yeast by co‐expressing CFA synthase from E. coli . Further enhancement of CFA yield is obtained applying a two‐stage bioprocess strategy. This work shows Saccharomyces cerevisiae is a promising host for high‐value CFA production.